Asia Pacific Forest Genetic Resources Programme - brochure - Asia Pacific Forest Genetic Resources Programme (2014)
Among the World’s continents, Asia has the highest number of tree species that are actively managed, for diverse purposes such as timber, non-timber products, energy and other ecosystem services – a reflection of the enormous cultural diversity of human populations in the continent. At the same time, more than 1700 of Asia’s tree species are threatened with extinction.APFORGEN, established in 2003, works to enhance the conservation and sustainable use of tree species and their genetic diversity in Asia and the Pacific.APFORGEN is the only network in Asia and thePacific that specifically focuses on the conservation and sustainable use of the genetic diversity of trees.